2011
DOI: 10.1039/c0cp02797a
|View full text |Cite
|
Sign up to set email alerts
|

Novel ice structures in carbon nanopores: pressure enhancement effect of confinement

Abstract: We report experimental results on the structure and melting behavior of ice confined in multi-walled carbon nanotubes and ordered mesoporous carbon CMK-3, which is the carbon replica of a SBA-15 silica template. The silica template has cylindrical mesopores with micropores connecting the walls of neighboring mesopores. The structure of the carbon replica material CMK-3 consists of carbon rods connected by smaller side-branches, with quasi-cylindrical mesopores of average pore size 4.9 nm and micropores of 0.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The structure of confined ice has been studied in carbon nanotubes of 0.7-1.5 nm diameter using molecular simulation 8,9 and experiment, 5,10 and provides convincing evidence for the formation of various kinds of ice nanocrystals, including square-gonal ice as ice VIII and ice IX in nanotubes of small diameters. 11 Similar quasi-high pressure effects due to confinement are observed in chemical reactions in pores. Reactions that only occur at high pressures in the bulk phase occur readily at normal bulk phase pressures in the confined phase as has been observed in experiments 12 and molecular simulations.…”
Section: Introductionmentioning
confidence: 61%
“…The structure of confined ice has been studied in carbon nanotubes of 0.7-1.5 nm diameter using molecular simulation 8,9 and experiment, 5,10 and provides convincing evidence for the formation of various kinds of ice nanocrystals, including square-gonal ice as ice VIII and ice IX in nanotubes of small diameters. 11 Similar quasi-high pressure effects due to confinement are observed in chemical reactions in pores. Reactions that only occur at high pressures in the bulk phase occur readily at normal bulk phase pressures in the confined phase as has been observed in experiments 12 and molecular simulations.…”
Section: Introductionmentioning
confidence: 61%
“…A fluid confined in a nanopore would become inhomogeneous, and as a result, some physical properties can be influenced by the dimension of the cavity. ,,,, Therefore, it is of interest to investigate the effect of radius of the cavity on the pressure profiles. Figure a,b shows the pressure profiles of the associating LJ fluid under the conditions of f = 4, ρ b σ 3 = 0.5, and βε ass = 5 for R increasing from 2.5σ to 20.0σ with an interval of 2.5σ.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the existing experiments and simulations on various properties of confined fluids, it was shown that some phenomena that can only be observed at a very high pressure in the bulk fluid can take place at a pressure that is orders of magnitude lower. Such an enhancement of pressure due to the nanoconfinement has attracted increasing interest. ,, Thus, one can expect that fluids within nanopores or porous materials have the scope for rapid development in the field of novel functional materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations